The Implementation of Value Chain Holistic Model of Ulos Weaving Fabric Creative Industry - Dameria Naibaho; Arlina Pratiwi Purba; Anggiat Situngkir; Jojor Lisbet Sibarani (Return : Study of Management, Economic and Bussines, 2024)
This research has a long-term goal to increase the income of stakeholders in the us weaving fabric industry in North Sumatra and the National Gross Domestic Product in Indonesia. The specific target to be achieved is to improve the concept of a value chain holistic model of the Ulos weaving fabric industry, which will soon be implemented. The methods used in achieving this goal are an experimental study by a value chain holistic model of the Ulos weaving fabric industry using the strength and opportunities strategy. Through a Focus Group Discussion involving MUSRENBANG, KOPERINDAG, City Government, Provincial Government, Ulos Weaving Fabric Manufacturers Group, Weaver Group, and Producers Cooperative, information and data will be collected, which will be grouped into Strengths, Weaknesses, Opportunities, and Threats information. The evaluation of data and information through a SWOT analysis shows the results that the proposed model is good and continues to implement a production and marketing strategy, where the establishment of a production cooperative will strengthen SMEs with a joint commitment of members and will facilitate the capital. The Association of SMEs was formed to produce quality production and standardized prices so as to be able to deal with internal competition properly, which will be able to support the Lake Toba tourist destination as a tourism activity in North Sumatera. Standing for marketing is also needed to support the construction of toll roads along the Lake Toba area through the tourist gateways of Medan and Silangit.